International perspectives on the ethics and regulation of human cell and tissue transplantation - Annette Schulz-Baldes; Nikola Biller-Andorno; Alexander Morgan Capron (The World Health Organization, 2007)
The transplantation of human cells and tissues has become a global enterprise for both life-saving and life-enhancing purposes. Yet current practices raise numerous ethical and policy issues relating to informed consent for donation, profit-making, and quality and safety in the procurement, processing, distribution, and international circulation of human cells and tissues. This paper reports on recent developments in the international debate surrounding these issues, and in particular on the attention cell and tissue transplantation has received in WHO's ongoing process of updating its 1991 Guiding principles on human organ transplantation. Several of the organizers of an international working group of stakeholders from a wide range of backgrounds that convened in Zurich in July 2006 summarize the areas of normative agreement and disagreement, and identify open questions regarding facts and fundamental concepts of potential normative significance. These issues must be addressed through development of common medical, scientific, legal and ethical requirements for human cell and tissue transplantation on a global basis. While guidance must accommodate the distinct ethical issues raised by activities involving human cells and tissues, consistency with normative frameworks for organ transplantation remains a prime objective.